Z Source Inverter Topologies-A Survey - V. Saravanan; M. Aravindan; V. Balaji; M. Arumugam (Institute of Advanced Engineering and Science, 2017)
Need for alternative energy sources to satisfy the rising demand in energy consumption elicited the research in the area of power converters/inverters. An increasing interest of using Z source inverter/converter in power generation involving renewable energy sources like wind and solar energy for both off grid and grid tied schemes were originated from 2003. This paper surveys the literature of Z source inverters/converter topologies that were developed over the years.